2014
DOI: 10.5223/pghn.2014.17.4.232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of SymptomaticClostridium difficileInfection in Children: Conditions as Infection Risks and Whether Probiotics Is Effective

Abstract: PurposeThis study investigated the clinical presentations of symptomatic Clostridium difficile infection (CDI) in children.MethodsWe reviewed the medical records of 43 children aged <20 years who showed either positive C. difficile culture or C. difficile toxin test results between June 2010 and April 2014.ResultsOf the 43 patients (mean age 6.7 years), 22 were boys. Sixteen patients (37.2%) showed both positive C. difficile culture and toxin test results. Seventeen out of 43 children (39.5%) had preexisting g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(28 reference statements)
0
13
1
Order By: Relevance
“…One meta-analysis has suggested that probiotics prophylaxis can result in a large reduction in CDI without increasing clinically important adverse events [25]. On the other hand, other researchers have suggested that routine use of probiotics might not be effective in preventing CDI [2627]. In the present study, colonization of C. difficile was not associated with the use of probiotics.…”
Section: Discussioncontrasting
confidence: 44%
“…One meta-analysis has suggested that probiotics prophylaxis can result in a large reduction in CDI without increasing clinically important adverse events [25]. On the other hand, other researchers have suggested that routine use of probiotics might not be effective in preventing CDI [2627]. In the present study, colonization of C. difficile was not associated with the use of probiotics.…”
Section: Discussioncontrasting
confidence: 44%
“…There is growing evidence that C. difficile is associated with diarrhea and increased lengths of hospital stays in children under 2 years of age535455. C. difficile infections may be underreported in this population, as it is often not associated with the severe outcomes observed in infected adults such as colon resection and mortality53.…”
Section: Discussionmentioning
confidence: 99%
“…Promising, but conflicting, results of efficacy have been shown in the adult population receiving S. boulardii or a mix of Lactobacilli. [37][38][39][40][41] However, in pediatric age the evidence is limited to case reports, 42,43 and RCTs that include the treatment of CDI as primary outcome are still lacking.…”
Section: Treatmentmentioning
confidence: 99%